A case of anti-VGKC antibody encephalitis and prolonged encephalopathy despite spontaneous resolution of imaging abnormalities. Issue 6 (1st November 2020) - Novoselova, Victoria; Kumar, Vikas; Singh, Niranjan N.; Lacasse, Alexandre
ABSTRACT: Anti-voltage-gated potassium channel (anti-VGKC) antibody encephalitis is a common form of autoimmune encephalitis (AE). AE is usually associated with autoimmune diseases or paraneoplastic phenomena such as seen in small cell lung cancer. Clinical presentation can include memory impairment, seizures, and psychiatric symptoms. We report a case of a 72-year-old male with non-small lung cancer in remission who presented with erosive gastritis and acute severe encephalopathy. Anti-VGKC antibody limbic encephalitis was diagnosed. Spontaneous resolution of encephalitis-associated changes on brain Magnetic Resonance (MR) with concomitant decreased circulating antibody levels were observed despite lack of overall cognitive improvement. Abbreviations: AE: autoimmune encephalitis; AMPAR: antibody limbic encephalitis - anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis; Anti-VGKC encephalitis: anti-Voltage-gated potassium channel antibody encephalitis; CRP: c-reactive protein; CT: computed tomography; EEG: electroencephalography; ESR: erythrocyte sedimentation rate; GCS: Glasgow Coma Scale; MRImaging: Magnetic resonance imaging; NMDA-R encephalitis: Anti-N-methyl D-aspartate receptor encephalitis; PCR: polymerase chain reaction.